2019
DOI: 10.2147/ott.s205760
|View full text |Cite
|
Sign up to set email alerts
|

<p>NEDD9 overexpression predicts poor prognosis in solid cancers: a meta-analysis</p>

Abstract: Background: The oncogenicity of neural precursor cell-expressed developmentally down-regulated 9 (NEDD9) has been demonstrated in multiple cancer types. However, the prognostic value of NEDD9 in some solid cancers remains controversial. Thus, this meta-analysis was conducted to evaluate the relationship between NEDD9 expression survival rates in solid tumors. Method: Our meta-analysis included studies searched from various search engines with specific inclusion criteria and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…In a subgroup analysis of patients with and without lymph node metastases, there were no significant differences in Cx43 and NEDD9 expression in patients without lymph node metastases , but patients with lymph node metastases showed higher expression of epithelial NEDD9 (Table 1, Figure 2). (14,(16)(17)(18)(19). Similar as in our study, expression of NEDD9 was found significantly increased in the tissue of pancreatic ductal adenocarcinoma compared to adjacent pancreatic tissue (18), but the same was not established in colorectal cancer (19).…”
Section: Predicting 2-year Survivalsupporting
confidence: 84%
“…In a subgroup analysis of patients with and without lymph node metastases, there were no significant differences in Cx43 and NEDD9 expression in patients without lymph node metastases , but patients with lymph node metastases showed higher expression of epithelial NEDD9 (Table 1, Figure 2). (14,(16)(17)(18)(19). Similar as in our study, expression of NEDD9 was found significantly increased in the tissue of pancreatic ductal adenocarcinoma compared to adjacent pancreatic tissue (18), but the same was not established in colorectal cancer (19).…”
Section: Predicting 2-year Survivalsupporting
confidence: 84%
“…8 It is not surprising that aberrant NEDD9 expression has been linked to the prognosis of human cancers. 8,20 In this study, we for the first time revealed that NEDD9 overexpression, identified from NEDD family, was associated with poor prognosis in AML. Notably, NEDD9 expression might act as a potential biomarker predicting prognosis and guiding treatment choice between chemotherapy and HSCT in AML.…”
Section: Discussionmentioning
confidence: 74%
“… 18 , 19 Overexpression of NEDD9 has now been strongly linked to poor prognosis in various types of cancers, as well as resistance to first‐line chemotherapeutics. 20 However, NEDD9 exhibits opposite effects regarding migratory capacity on myeloid cells as compared to epithelial or lymphoid cells, which block migration and dissemination of neoplastic cells of the myeloid lineage, while stimulating them in solid tumours or lymphoid neoplasias. NEDD9 −/− mice show an increased number of macrophages, and a simultaneous reduction of B lymphocytes in peripheral blood 21 and secondary lymphoid organs, yielding an almost complete loss of marginal zone B cells in the spleen.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 NEDD9 has been implicated in the invasion ability of several tumors and has been speculated to be a candidate biomarker of invasiveness for lung cancer, breast cancer, melanoma, colon cancer and pancreatic cancer. 17,25,26 The function of NEDD9 related to cancer metastasis has focused on the FAK, Src and Akt signaling pathways. 27 The interactions of NEDD9 with FAK and Src led to the tyrosine phosphorylation of NEDD9 to create binding sites for effector proteins to facilitate cell migration.…”
Section: Dovepressmentioning
confidence: 99%